(untitled) (International Journal of Engineering Sciences & Management Research, 2014)
One of the most important criteria for performance evaluation is stock return. It is defined based on EPS, share price to EPS ratio or other criteria. In this paper we determined the relation between stock return with operating cash flow based on Iranian Co. performance. Using fixed firm effects in factors of regression method selected for a sample from Tehran exchange market containing about 54 firms during a six financial year’s analysis. In this paper, the relation between dependent and independents variables was evaluated based on multi-variables linear-regression. The results showed that; the operating cash flow, profitability and the returns of all stakeholders had a significant relationship. However, with increasing profitability and cash flow of information asymmetry in proportion to their correlation with the economic efficiency of shareholder returns. Also refer to the information content of accounting figures, no further explanation is the cash flow Information asymmetry in the relationship between accounting numbers and cash flow model to determine the performance of Gunther is the company’s stock return is offered in Tehran Stock Exchange. .Hence one-size-fit-all performance measures are provided for performance measurement in managerial accounting.